Chemomodulation of human dendritic cell function by antineoplastic agents in low noncytotoxic concentrations - Kaneno, Ramon [UNESP]; Shurin, Galina V.; Tourkova, Irina L.; Shurin, Michael R. (Biomed Central Ltd., 2009)
The dose-delivery schedule of conventional chemotherapy, which determines its efficacy and toxicity, is based on the maximum tolerated dose. This strategy has lead to cure and disease control in a significant number of patients but is associated with significant short-term and long-term toxicity. Recent data demonstrate that moderately low-dose chemotherapy may be efficiently combined with immunotherapy, particularly with dendritic cell (DC) vaccines, to improve the overall therapeutic efficacy. However, the direct effects of low and ultra-low concentrations on DCs are still unknown. Here we characterized the effects of low noncytotoxic concentrations of different classes of chemotherapeutic agents on human DCs in vitro. DCs treated with antimicrotubule agents vincristine, vinblastine, and paclitaxel or with antimetabolites 5-aza-2-deoxycytidine and methotrexate, showed increased expression of CD83 and CD40 molecules. Expression of CD80 on DCs was also stimulated by vinblastine, paclitaxel, azacytidine, methotrexate, and mitomycin C used in low nontoxic concentrations. Furthermore, 5-aza-2-deoxycytidine, methotrexate, and mitomycin C increased the ability of human DCs to stimulate proliferation of allogeneic T lymphocytes. Thus, our data demonstrate for the first time that in low noncytotoxic concentrations chemotherapeutic agents do not induce apoptosis of DCs, but directly enhance DC maturation and function. This suggests that modulation of human DCs by noncytotoxic concentrations of antineoplastic drugs, i.e. chemomodulation, might represent a novel approach for up-regulation of functional activity of resident DCs in the tumor microenvironment or improving the efficacy of DCs prepared ex vivo for subsequent vaccinations.